Incest: Honor thy father, brother / Felicia Ferdinand... [et al...] - Ferdinand, Felicia; Ahmin, Irene; Liun, Julin; M Cyrillus, Judith; Flavinus, Naomi (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 1998)
Increasing public awareness of Incest and child sexual abuse through media coverage, documentaries, films, studio discussion programs and setting up of children in the United Kingdom has focused attention on the many children who suffer from the unwanted sexual attention of fathers, mothers, stepfathers, grandfathers grandmothers, brothers, aunts, uncles, cousins, friends of the family, neighbors or youth leader, as well as other male or female authority figures. Well, publicized cases of child sexual abuse that have been brought to the attention of social services or the courts, including the lengthy inquiry into Cleveland, have ensured that incest and child sexual abuse is kept to the forefront of public consciousness. The emphasis is on the plight of the children and much of the available resources are being poured into the training of social workers, mental health professional and police to provide effective intervention when sexual is disclosed or reported. Of necessity the priority is on helping those children that are currently being sexually abused. Resources are limited and not all children who have disclosed are provided with the type of support and therapeutic intervention which will ameliorate the possible long term effects associated with the sexual abuse and its disclosure. Although increasing numbers of children appear to be disclosing their abuse, there are probably many more children who do not and, as a consequence of not disclosing, continue to be sexually assaulted.